MACROECONOMICS AS DETERMINANTS OF THE MONEY SUPPLY IN INDONESIA: ERROR CORRECTION MODELS ANALYSIS - Ashari, Nesha Rizky; Prasasti, Riska; Afandi, Akhsyim (Jurnal Ilmiah Ekonomi Bisnis, 2025)
This study analyzes macroeconomic factors that affect the money supply in Indonesia during the period 1993-2022, using the Error Correction Model (ECM). The main objective of this study is to identify macroeconomic variables that are significant in determining the money supply, as well as to understand the short-term and long-term dynamics of these variables. The results of the analysis show that the variables of exchange rate, GDP, government expenditure, and interest rates have a negative effect on the money supply, as is the case with FDI and inflation. Both long-term and short-term actually have a negative impact on the money supply in Indonesia. ECM managed to capture the short-term and long-term relationships between these macroeconomic variables and the money supply. These findings provide important insights for policymakers in formulating effective monetary strategies to manage the money supply and maintain economic stability.